Sustaining China's economic growth in the twenty-first century - Yao, Shujie; Liu, Xiaming, 1954- (RoutledgeCurzon studies on the Chinese economy, 2003)
Economic growth in China has been exceptionally strong in recent decades, but the country still faces enormous economic problems, including huge poverty, uneven regional development, the problems associated with strengthening capital formation, modernising and making more productive the very large former state sector. This book presents the work of a wide range of leading economists of China, all members of the prestigious Chinese Economics Association, who put forward new research findings and new thinking on a wide range of issues connected with the problem of sustaining China's economic growth.